Notch signaling between cerebellar granule cell progenitors - Adachi, Toma; Miyashita, Satoshi; Yamashita, Mariko; Shimoda, Mana; Okonechnikov, Konstantin; Chavez, Lukas; Kool, Marcel; Pfister, Stefan; Inoue, Takafumi; Kawauchi, Daisuke; Hoshino, Mikio (eNeuro, 2021)
Visual Abstract - - Download figureOpen in new tabDownload powerpoint - Cerebellar granule cells (GCs) are cells which comprise over 50% of the neurons in the entire nervous system. GCs enable the cerebellum to properly regulate motor coordination, learning, and consolidation, in addition to cognition, emotion and language. During GC development, maternal GC progenitors (GCPs) divide to produce not only postmitotic GCs but also sister GCPs. However, the molecular machinery for regulating the proportional production of distinct sister cell types from seemingly uniform GCPs is not yet fully understood. Here we report that Notch signaling creates a distinction between GCPs and leads to their proportional differentiation in mice. Among Notch-related molecules, Notch1, Notch2, Jag1, and Hes1 are prominently expressed in GCPs. In vivo monitoring of Hes1-promoter activities showed the presence of two types of GCPs, Notch-signaling ON and OFF, in the external granule layer (EGL). Single-cell RNA sequencing (scRNA-seq) and in silico analyses indicate that ON-GCPs have more proliferative and immature properties, while OFF-GCPs have opposite characteristics. Overexpression as well as knock-down (KD) experiments using in vivo electroporation showed that NOTCH2 and HES1 are involved cell-autonomously to suppress GCP differentiation by inhibiting NEUROD1 expression. In contrast, JAG1-expressing cells non-autonomously upregulated Notch signaling activities via NOTCH2-HES1 in surrounding GCPs, eventually suppressing their differentiation. These findings suggest that Notch signaling results in the proportional generation of two types of cells, immature and differentiating GCPs, which contributes to the well-organized differentiation of GCs.